Living worth : value and values in global pharmaceutical markets - Ecks, Stefan (Critical global health., 2022)
"In Living Worth Stefan Ecks draws on ethnographic research on depression and antidepressant usage in India to develop a new theory of value. Framing depressive disorder as a problem of value, Ecks traces the myriad ways antidepressants come to have value, from their ability to help make one's life worth living to the wealth they generate in the multibillion-dollar global pharmaceutical market. Through case studies that include analyses of the different valuation of generic and brand name drugs, the origins of rising worldwide depression rates, and the marketing, prescription, and circulation of antidepressants, Ecks theorizes value as a process of biocommensuration. Biocommensurations-transactions that aim or claim to make life better-are those forms of social, medical, and corporate actions that allow value to be measured, exchanged, substituted, and redistributed. Ecks's theory expands value beyond both a Marxist labor of theory of value and a free-market subjective theory, thereby offering new insights into how the value of lives and things become entangled under neoliberal capitalism"--